Unveiling the Importance of Precursor Preparation for Highly Efficient and Stable Phenethylammonium‐Based Perovskite Solar Cells. Issue 4 (3rd April 2020) - Lee, Da Seul; Kim, Jincheol; Bing, Jueming; Zheng, Jianghui; Yun, Jae Sung; Seidel, Jan; Lim, Sean; Green, Martin A.; Huang, Shujuan; Ho-Baillie, Anita W. Y.
Abstract : Precursor Preparation In article number 1900463, Anita W. Y. Ho‐Baillie and co‐workers report the use of two precursor preparation methods for the deposition of phenethylammonium‐containing organic‐inorganic hybrid perovskite fi lms for photovoltaic a pplications. The fi lm properties, photovoltaic device performance, and stability differ depending on the precursor preparation methods. These new insights are important for optimising precursor preparations for lower dimensional perovskite fi lms to achieve the best device performance and stability.